Distribution of human papillomavirus (HPV) genotypes in genital warts from males in Slovenia - Potočnik, Marko (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2007)
Background: Genital warts (GWs) are the most frequent benign tumors in the anogenital region of both males and females. Human papillomaviruses (HPV) are etiologically associated with the development of virtually all GWs. HPV-6 and HPV-11 are the most commonly detected HPV genotypes, but at least 20 other alpha-HPV genotypes have occasionally been found in GW tissue specimens. Objective: There is limited knowledge of GWs in Slovenia. Thus in this study we tested 55 GW tissue specimens collected from the same number of male patients using 2 different PCR protocols to obtain the first data concerning HPV and GWs in Slovenia. Material and methods: 55 GW tissue specimens were tested for the presence of HPV using PGMY09/ PGMY11 and CPI/CPllg polymerase chain reaction (PCR). HPV genotypes were determined using restriction fragmentlength polymorphism analysis of PGMY09/11 PCR products or by sequencing of the CPI/CPllg PCR products. In some GWs, the genotyping results were also confirmed using the Linear Array HPV Genotyping Test. Results: HPV DNA was detected in all 55 tissue specimens of GWs. HPV-6 or HPV-11 was detected in 53 cases of GWs, and HPV-44 and candHPV-91 in one GW each. HPV-6 was detected approximately 4 times more frequently than HPV-11. In addition, HPV-16, HPV-31, HPV-51, HPV-53, HPV-55, candHPV62, HPV-66, HPV-70, HPV-73, andHPV-84 were detected in some GW specimens. According to the published data,our study is the first to report the presence of candHPV-62 and candHPV-91 in GW tissue specimens. Conclusions: Our study showed that HPV can be found in virtually all GW tissue specimens obtained from male patients in Slovenia. Because HPV-6 or HPV-11 was detected in 96.4% of GWs studied, it seems that, if a quadrivalent HPV vaccine proves to be effective in males, this vaccine could prevent the great majority of incidental GWs in males in Slovenia.
Keywords: Classification; Condylomata Acuminata; Genotip; Genotype; Kondilomata akuminata; man; moški; Papillomavirus, Human; papiloma virusi; Papilomavirus človeški; Polimerazna, verižna reakcija; Polymerase Chain Reaction; Slovenia; Slovenija